PENGARUH PEMBERIAN TAPE KETAN HITAM TERHADAP KOLESTEROL LOW DENSITY LIPOPROTEIN (LDL) - Roro Nur Fauziyah; Fitriani Nurjannah; Surmita Surmita (Poltekkes Kemenkes Bandung, 2020)
Food antioxidants have been widely used as functional and bias to lower Low Density Lipoprotein (LDL) cholesterol. This study is intended to determine the effect of black sticky ribbon on the decrease of LDL cholesterol levels. This research is two groups of pre and post experiment design. The population of this study is Desa Budiharja, Kecamatan Cililin, Kabupaten Bandung Barat over the age of 35 years. Sampling using Random Sampling method by Simple Random Sampling. The sample size was 19 people in each group. The Fermented Glutinous Black Rice is given 200gr / day black sticky rice and low fat diet counseling. The control group was given low-fat diet counseling. Statistical test results using Dependent T-test showed high active LDL cholesterol levels before and after treatment in the black glutinous band group with p <0.001 (p≤0.05) and in the control group there was no significant decrease in LDL cholesterol With value p = 0,452 (p> 0,05). The result of statistic test using Mann-Whitney showed the effect of black sticky ribbon on the decrease of LDL cholesterol with p = 0,011 (p> 0.05). Need to do socialization of Fermented Glutinous Black Rice as an alternative functional ingredient to lower LDL cholesterol levels.